The Influence of Corporate Governance on Financial Performance Mediated by Gender Diversity - Tee, Lee Siew; Nizam, Ismail (Journal of Asian Business Strategy, 2020)
Corporate governance (“CG”) practices have raised a concerned issue by many countries worldwide particularly Asian countries following the Asian Financial Crisis in 1997 including Malaysia. Malaysian Code on Corporate Governance (MCCG) was first introduced in year 2000, revised in 2007, 2012 and culminating in the new supercharged 2017 version. CG has form part of the Listing Requirements of Bursa Malaysia Securities Berhad (Bursa Securities) that must be complied with by a listed issuer and its directors. The aim of this survey-based research administered 250 questionnaires to the middle and top-level managers of Malaysian firms to examine the influence corporate governance practiced in the country. Many researches on corporate governance in Malaysia are based secondary data and hence the questionnaires are designed to critically examine the corporate governance (board structure, CEO duality, audit/risk management committee and corporate reporting) on financial performance of Malaysian organisations in terms of sales, profitability, return on equity and share price. Further research on mediating effect of gender diversity may help to provide a basis for paradigm shift and result in better representation of gender at the level of decision making and in influencing corporate governance on the performance of the companies. The research found that the corporate governance variables overall have no significant impact to explain the performance of the listed companies. It suggests future researchers to explore into other factors that could possibly affect the company performance.